Effects of a flexibly delivered group-based acceptance and commitment therapy on reducing stress and enhancing psychological wellbeing in parents of school-age children during the COVID-19 pandemic: a quasi-experimental study - Mak, Yim-Wah; Leung, Doris Y. P.; Zhang, Xuelin; Chung, Joyce O. K.; Chow, Petsy S. Y.; Ruan, Jiayin; Yeung, Jerry W. F. (Frontiers in Public Health, 2024)
IntroductionCOVID-19 has increased parental stress and significantly impacted the psychological well-being of individuals, especially parents of school-age children. Acceptance and Commitment Therapy posits that individuals can accept their unchangeable inner experiences (thoughts and feelings) while acting in ways aligned with their personal values, demonstrating effectiveness in reducing stress and improving psychological well-being, especially among parents of children with chronic illness. This study aimed to test the effectiveness of a group-based ACT, delivered flexibly, in improving stress and psychological well-being in parents with school-age children, regardless of their children’s chronic conditions, within a real-world context.MethodsThis quasi-experimental study recruited parents with school-age children, through convenience sampling from the Christian Family Service Centre in Hong Kong. The group-based Acceptance and Commitment Therapy intervention consisted of five weekly sessions delivered via face-to-face meetings and online videoconferencing, consistent with participants’ preferences and COVID-19 related restrictions in Hong Kong. Paired t-tests and Generalized Estimating Equations following the intention-to-treat principle were used to examine the overall effects and the moderating effects of delivery methods.ResultsThe study included 250 parents, with an average age of 40.90 years, mostly women. The average age of their youngest child was 7.68 years. In line with COVID-19-related restrictions and participants’ preferences, 109 parents participated in online sessions, while 141 attended face-to-face sessions. Results showed significant small-to-medium improvements in various outcome variables after the intervention, including parental stress (Cohen’s d = 0.26), general stress (d = 0.18), depressive symptoms (d = 0.18), mental health literacy (d = 0.43), subjective wellbeing (d = 0.25), and psychological flexibility (d = 0.28). Notably, the online videoconferencing format was found to be as effective as the face-to-face format, with similar session attendance rates.ConclusionThe findings highlight the potential of group-based Acceptance and Commitment Therapy to alleviate stress and improve psychological well-being in parents of school-age children, regardless of the delivery method, especially during crises such as the COVID-19 pandemic. However, due to limitations in the study design, caution is warranted when interpreting the overall effects of group-based ACT on parent outcomes and the moderating role of delivery methods. Further research is needed to validate these findings and explore the nuances of delivery methods in similar real-world situations.